Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Good evening to everybody! I have to check if the following two functions are Gâteaux differentiable:

$$ (a)~~f(x_1,x_2)=x_1^2x_2~~~~~~~~~~(b)~~f(x_1,x_2,x_3)=(x_1-x_2)\exp(x_3) $$

(a) Is it enough only to name the Gâteaux derivation $\eta$ in any $x\in\mathbb{R}^2$ for any direction $h\in\mathbb{R}^2$?

My calculation gave me $$ \eta=Df(x)[h]=x_1\cdot (2x_2h_1+x_1h_2). $$

Is that enough or is some additional argumentation necessary here?

(b) I do not come along completely with this. My calculation ended here:

$\lim\limits_{t\to 0}\frac{f(x+th)-f(x)}{t}=\lim\limits_{t\to 0}\left[\frac{x_1\exp(x_3+th_3)}{t}+h_1\exp(x_3+th_3)-\frac{x_2\exp(x_3+th_3)}{t}-h_2\exp(x_3+th_3)-\frac{(x_1-x_2)\exp(x_3)}{t}\right]$

What is the next step here? To my opinion the limits do not exist for the fractions but do exist for the other summands. I am a little bit confused...

Can anybody please help me?

Thank you very much and greetings! math12

share|cite|improve this question
If $f$ is Fréchet differentiable, then $d f (x;h) = Df(x) h$, so your calculation is sufficient. – copper.hat Jan 28 '13 at 17:07
How do I know that (a) is Fréchet differentiable? – math12 Jan 28 '13 at 17:09
Both functions $f$ are smooth. – copper.hat Jan 28 '13 at 17:22
I am sorry, I do not understand what you mean. – math12 Jan 28 '13 at 17:28
up vote 1 down vote accepted

The Gâteaux differential is just the derivative of the function along the line $t \mapsto x+th$, at the point $t=0$.

In both cases above consider the function $\phi(t) = f(x+th)$, and note that $df(x;h) = \phi'(0)$.

So, for (a), $\phi(t) = (x_1+h_1 t)^2 (x_2+h_2 t)$, from which we obtain $df(x;h) = \phi'(0) = x_1(2 h_1 x_2+h_2 x_1)$, which is what you have above.

For (b), $\phi(t) = (x_1-x_2-h_2 t+h_1 t) e^{(x_3+h_3 t)}$, from which we obtain $df(x;h) = \phi'(0) =(h_1-h_2+h_3(x_1-x_2))e^{x_3}$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.